Forage Planting and Establishment Methods - Yoana C. Newman; Joao Vendramini; Carroll G. Chambliss; Martin B. Adjei (EDIS)
Establishment of an excellent, uniform stand of forage in a short period of time is important. The producer needs to do everything possible to ensure successful establishment. Several requirements that must be met are briefly discussed, along with various planting methods. This revised 7-page fact sheet was written by Y.C. Newman, J. Vendramini, C.G. Chambliss, M.B. Adjei, and published by the UF Department of Agronomy, April 2011.